THE EXPOSURE OF ACEH HEROINE NARRATIVE: A POTENTIAL TOOL TO PROMOTE GENDER EQUALITY - Muhammad Iqhrammullah (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2018)
Despite many ratifications of international agreement on gender equality by Indonesia, the women still face many kinds of gender-based discrimination. In Aceh’s communities there found a resistance to gender equality due to the contradicting value with religion and culture. Education, in the other hand, could play an important role to reduce gender inequality, but should be incorporated with the changing in religion and culture. Aceh in history, was never out of stock producing women leaders (heroine), most prominently Ratu Safiatudin, Laksamana Malahayati, and Cut Nyak Dien. Aceh heroine narrative was found to be a potential tool to tackle inequality among men and women. This study suggests three major findings regarding the exposure: 1) There was a lacking of integrated gender equality education in the narratives, 2) The cognitive dissonance occurrence and 3) The exposure motivated boys to be more competitive against girls. Overall, the exposure of Aceh heroine narratives gave positive effect for boys to increase their competitiveness and acknowledge women’s capabilities, meanwhile for girls they became inspired in pursuing their dreams and even to lead.